Law of Approach to Saturation for Determining Magnetic Intrinsic Behavior of BaFe12-xMnx/2Tix/2O19 and SrFe12-xMnx/2Tix/2O19 - Rafael F Maniur; Adam Badra Cahaya; Azwar Manaf (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2021)
The problem with permanent magnetic materials of very high anisotropic fields is that it is still difficult to determine the intrinsic magnetic properties, when measured using a magnetometer which has a limited magnetic field. The Law of Approach to Saturation (LAS) mathematical model provides a way to measure permanent magnets, with high anisotropic fields by correcting the magnetization data of the first quadrant curve or the virgin curve of the minor hysteresis loop. In this research, a computational LAS program was conducted to compute the intrinsic magnetic properties of magnetic materials, such as saturation magnetization, anisotropy field and magnetocrystalline anisotropy constant. Magnetization data were obtained from permagraph measurements of barium hexaferrite (BaFe12O19), strontium hexaferrite (SrFe12O19) and microwave absorbers BaFe12-xMnx/2Tix/2O19 and SrFe12-xMnx/2Tix/2O19. The convergences of magnetization were assessed to determine the effect of substitution on barium hexaferrite and strontium hexaferrite materials on saturation magnetization values, anisotropy constants and anisotropic fields.